Does nifedipine improve outcomes of embryo transfer?: Interim analysis of a randomized, double blinded, placebo-controlled trial. Issue 4 (January 2019) - Ng, Kelvin Kwok Lap; Rozen, Genia; Stewart, Tanya; Agresta, Franca; Polyakov, Alex
Abstract: Background: Implantation failure is the main factor affecting the success rate of in vitro fertilization (IVF) procedures. Studies have reported that uterine contractions (UC) at the time of embryo transfer (ET) were inversely related to implantation and pregnancy rate, hence reducing the success of IVF treatments. Various pharmacological agents, with the exception of calcium channel blockers, have been investigated to improve ET outcomes by reducing UC. Thus, a double-blinded randomized, placebo-controlled trial was conducted to determine whether nifedipine, a calcium channel blocker with potent smooth muscle relaxing activity and an excellent safety profile, can improve the outcome of patients undergoing ET treatments. Methods: Ninety-three infertile women were recruited into 1 of 2 groups: placebo (n = 47) or nifedipine 20 mg (n = 46). Study participants were admitted 30 minutes prior to ET and given either tablet after their baseline vital signs were recorded. They then underwent ET and were observed for adverse events for another 30 minutes post-ET. Follow up of the participants' outcomes was conducted via electronic medical records. The primary outcomes are implantation and clinical pregnancy rates. Secondary outcomes include any maternal or fetal adverse events, miscarriage, pregnancy, live births, and neonatal outcomes. Resulting data were then analyzed using t test, Pearson chi-square test, and Fisher exact test to compare outcomes between the 2 groups. Results: No statistical differences in the implantation rate (42.6% vs 39.1%, P = .737, rate ratio 0.868, 95% confidence interval [CI]: 0.379–1.986) and the clinical pregnancy rate (23.4% vs 26.1%, P = .764, rate ratio 1.155, 95% CI: 0.450–2.966) were detected between the placebo and the treatment groups. In addition, no statistical significance between the placebo and the treatment groups for any secondary outcomes were detected. Conclusions: This double blinded, randomized, and placebo-controlled trial demonstrated that the single use of 20 mg nifedipine given 30 minutes before embryo transfer did not improve the implantation rate or the clinical pregnancy rate of the infertility treatment. Further studies are required to demonstrate the clinical benefits and risks of nifedipine usage in embryo transfer. Abstract : Supplemental Digital Content is available in the text